2016
DOI: 10.5539/ijbm.v11n6p118
|View full text |Cite
|
Sign up to set email alerts
|

Compensation Committee Quality and Effective Executive Remuneration

Abstract: Grounding in the agency theory, this paper questions whether high quality compensation committee influences the design of executive remuneration towards the alignment of the contrasting interests between managers and shareholders. Relying on a comprehensive approach that captures the compensation committee quality based on different attributes (i.e. independence, interlocking directorates, directors appointed by minorities) we conduct a two-step empirical analysis. First, we illustrate the evolution over time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 53 publications
0
4
2
Order By: Relevance
“…The interaction between the variation in the market value with the existence of a remuneration committee (∆VM*CREM) and executive compensation was not significant. This result differs from the findings by Catuogno et al (2016) and Kanapathippillai et al ( 2019), which indicated a positive relationship between the presence of a remuneration committee and PPS. However, model 2 showed that the interaction of the variation in the market value with CEO duality (∆VM*DCEO) was positive and significant at a 5% level.…”
Section: Descriptive Analysiscontrasting
confidence: 99%
See 4 more Smart Citations
“…The interaction between the variation in the market value with the existence of a remuneration committee (∆VM*CREM) and executive compensation was not significant. This result differs from the findings by Catuogno et al (2016) and Kanapathippillai et al ( 2019), which indicated a positive relationship between the presence of a remuneration committee and PPS. However, model 2 showed that the interaction of the variation in the market value with CEO duality (∆VM*DCEO) was positive and significant at a 5% level.…”
Section: Descriptive Analysiscontrasting
confidence: 99%
“…This fundamental role places remuneration committees in an outstanding position in the literature that addresses their composition (Conyon, 2014;Strobl, Rama, & Mishra, 2016) mance (Catuogno et al, 2016;Conyon, 2014;Kanapathippillai et al, 2019). Aspects of the remuneration committee have been used in many countries as alternatives to connect the sensitivity of the CEOs' pay to the increase in firm performance.…”
Section: Executive Compensation and Pay-performance Sensitivitymentioning
confidence: 99%
See 3 more Smart Citations